Portfolio capital flows and economic growth: do institutional factors matter? - Murdipi, Rafiqa; Baharumshah, Ahmad Zubaidi; Law, Siong Hook (Elsevier, 2023)
This paper examines the impact of institutional qualities on country-specific pull versus push factors on portfolio flows and growth. The interplay among economic policy uncertainty (EPU), host country’s institutional quality and growth are systematically studied. The analysis reveals that social institutions matter in toning down risks associated with global interest rate. Political stability is vital in moderating the negative effects linked to EPU, while social cohesion mitigates the stressful (negative) effects of soaring debt–GDP ratios. Institutions and domestic conditions serve as devices to partially insulate economies from stress conditions, including the spillovers from the unconventional monetary policy originating from the frontier countries. Policy responses should emphasize on reforming institutions to smooth the fluctuations of portfolio capital inflows and to procure stronger growth. The empirical results show that democracy matters in the growth empiric. The economic-enhancing benefits of portfolio investments remain fairly robust to several measures of institutions.